The Phenomenon of MSMEs Performance in Magelang City During the Pandemic COVID-19 - Lionora, Clarisa Alfa; Yacobo P. Sijabat; Heni Hirawati; Hartono, Budi; Axel Giovanni (KINERJA, 2022)
Micro, Small, and Medium Enterprises (MSMEs) have a fundamental role in the regional economy as well as the national economy. This study aims to provide empirical evidence regarding the performance variability of MSMEs during the COVID-19 pandemic. The research population is all MSMEs in Magelang City. The research sample was 7,924 MSMEs obtained through purposive sampling. This study uses descriptive statistical analysis. The results and discussion show that the City of Magelang, from an economic perspective, has a fairly stable economic condition from 2015 to 2019. However, the COVID-19 pandemic in 2020 put the economy of Magelang City in a recession phase. Nevertheless, the competitiveness of Magelang City in 2020 has increased compared to 2019. The analysis of the variability of the performance of MSMEs shows that the South Magelang District has the lowest turnover of MSMEs. Central Magelang Subdistrict has the highest MSME turnover value. South Magelang Subdistrict has the highest average turnover of MSME compared to the average turnover of MSME in North Magelang and Central Magelang Districts.